Functionalization of vertically aligned carbon nanotubes - Van Hooijdonk, Eloise; Bittencourt, Carla; Snyders, Rony; Colomer, Jean-François (Beilstein Journal of Nanotechnology, 2013)
This review focuses and summarizes recent studies on the functionalization of carbon nanotubes oriented perpendicularly to their substrate, so-called vertically aligned carbon nanotubes (VA-CNTs). The intrinsic properties of individual nanotubes make the VA-CNTs ideal candidates for integration in a wide range of devices, and many potential applications have been envisaged. These applications can benefit from the unidirectional alignment of the nanotubes, the large surface area, the high carbon purity, the outstanding electrical conductivity, and the uniformly long length. However, practical uses of VA-CNTs are limited by their surface characteristics, which must be often modified in order to meet the specificity of each particular application. The proposed approaches are based on the chemical modifications of the surface by functionalization (grafting of functional chemical groups, decoration with metal particles or wrapping of polymers) to bring new properties or to improve the interactions between the VA-CNTs and their environment while maintaining the alignment of CNTs.
Keywords: aligned; carbon nanotubes; fluorination; functionalization; graphene; nitration; oxidation